Ocorrência de Mycobacterium leprae e investigação de Mycobacterium lepromatosis em pequenos mamíferos não-voadores no estado de Mato Grosso, Centro-Oeste do Brasil - Nogueira, Beatriz Silva (2023)
Leprosy is a chronic infectious disease caused by the bacilli Mycobacterium leprae and Mycobacterium lepromatosis. In addition to humans, animals such as nine-banded armadillos and red squirrels can also be naturally infected by M. leprae. The aim of this study was to detect the presence of M. leprae and M. lepromatosis in non-volant small mammals of the order Didelphimorphia and Rodentia using polymerase chain reaction (PCR) conventional and qPCR assay. Field expeditions were conducted in three municipalities in the Mato Grosso State, Midwest of Brazil during 2014 and 2018, in areas belonging to the Amazon and Cerrado biomes. A PCR assay using specific primers targeting the RLEP and RLPM genes of Mycobacterium leprae and Mycobacterium lepromatosis, respectively, was used to screen for these agents in small non-volant mammals. M. leprae DNA was detected in 13.8% of the samples. A multi-level model showed that the Cerrado biome had a strong association with the presence of M. leprae (OR: 53.5, p < 0.001). M. lepromatosis was not detected. This study is the first to report the detection of M. leprae in small non-volant mammals in Brazil.